A smartphone-integrated rapid and sensitive lateral flow test strip for quantitative detection of Fusarium spp. in maize samples - Rotamporn, Saowalak; Cheubong, Chehasan; Sansenya, Sompong; Jantra, Jongjit; Teepoo, Siriwan (My University, 2025)
In the world, maize is considered as one of the most valuable resources. Fusarium spp. are the primary soilborne plant-pathogenic fungi that can infect maize seeds and cause diseases that potentially decrease the production of crops. This study aims to develop a rapid and sensitive lateral flow test strip (LFTS) utilizing gold nanoparticles (AuNPs) for on-site detection of Fusarium spp. in maize samples. The smartphone-integrated LFTS enables the identification of Fusarium spp. within a concentration range of 0.2–1.5 nM and achieves a limit of detection (LOD) as low as 0.063 nM. The quantitative determination of the Fusarium spp. can be completed within 8 min. Maize samples were analyzed using both the LFTS and real-time polymerase chain reaction (real-time PCR). The LFTS demonstrated effective recovery in spiked samples, with values ranging from 80.1% to 101.1%. Furthermore, the real-time PCR results exhibited significant agreement with the LFTS results. Compared to the traditional real-time PCR technique, the proposed LFTS offers a sensitive, accurate, and rapid assay for the on-site detection of Fusarium spp. in maize samples.
Keywords: Fusarium spp.; Gold nanoparticle; Lateral flow test strip; Maize sample; Smartphone